Can sutures get wet? Prospective randomised controlled trial of wound management in general practice. Issue 7549 (24th April 2006) - Heal, Clare; Buettner, Petra; Raasch, Beverly; Browning, Sheldon; Graham, David; Bidgood, Rachel; Campbell, Margaret; Cruikshank, Robert
Abstract: Objective To compare standard management of keeping wounds dry and covered with allowing wounds to be uncovered and wet in the first 48 hours after minor skin excision. Design Prospective, randomised controlled, multicentre trial testing for equivalence of infection rates. Setting Primary care in regional centre, Queensland, Australia. Participants 857 patients randomised to either keep their wound dry and covered (n = 442) or remove the dressing and wet the wound (n = 415). Results The incidence of infection in the intervention group (8.4%) was not inferior to the incidence in the control group (8.9%) (P < 0.05). The one sided 95% confidence interval for the difference of infection rates was ∞ to 0.028. Conclusion These results indicate that wounds can be uncovered and allowed to get wet in the first 48 hours after minor skin excision without increasing the incidence of infection.